Predictors of Syphilis in the Population of Men Like Sex with Men (LSl) in 10 Regencies/Cities In Indonesia - Marta Butar Butar; Mondastri Korib Sudaryo; Puspita Sari (International Journal of Health Engineering and Technology, 2024)
Syphilis is a bacterial sexually transmitted infection (STI) caused by Treponema pallidum. This disease results in significant morbidity and mortality. This study aims to analyze the predictors of syphilis incidence in the MSM population, namely age, education level, HIV status, use of condoms, consumption of drugs/injecting drugs, alcohol consumption, number of sex partners and STI examinations. The research design is cross sectional using secondary data from the 2015 IBBS. The analysis used is Cox regression which estimates the Prevalence Ratio value. The proportion of syphilis infection in the MSM group in 10 districts/cities in Indonesia is 15.7%. There was a significant relationship between HIV status (PR 2.05 (95% CI 1.58-2.66), Age (20-24 years old PR 2.45 (95% CI 1.07-5.64), 25-24 years old. 29 years PR 3.01 (95% CI 1.30-6.95), > 30 years PR 2.42 (95% CI 1.04-5.65) versus 15-19 years), Alcohol (PR 1, 37 (95% CI 1.01-1.86), Education 1.45 (95% CI 1.02-2.06) with the incidence of syphilis infection in MSM while condom use, drugs, number of male sex partners and STI examinations were not statistically related with p value > 0.05.